Development of RRL AWBM model and investigation of its performance, efficiency and suitability in Shipra River Basin - TRIVEDI, AYUSHI; GALKATE, R. V.; GAUTAM3, VINAY KUMAR; PYASI, S. K. (Journal of Soil and Water Conservation, 2021)
The current study demonstrates the potential use of RRL AWBM model for river flow modeling by developing a rainfall-runoff relationship for Shipra river basin in India. Daily data of rainfall, discharge, and evaporation for 21 years (from 1990 to 2010) have been used for modelling. Model parameters were calibrated using 11 years of data and rest of the data are used for model validation. Statistical approach and various supporting model including CROPWAT 8.0 model has been used to find out the model input. Optimum architectures of the models are selected according to the obtained evaluation criteria in terms of Nash–Sutcliffe efficiency coefficient and root mean squared error. Result of this study has been compared in avenue of RRL AWBM model. The results of this study indicate that the Nash Sutcliffe Efficiency for calibration was found to be 82.30% and 64.57% for the validation period. The model performs better in estimating the hydrograph characteristics such as flow duration curve effectively.